2022
DOI: 10.3389/fpubh.2022.888168
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: A Potential Mitigation Tool for the Endemic Stage of the COVID-19 Pandemic?

Abstract: The impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and associated development of clinical symptoms of COVID-19 have presented an enormous global impact on our health care systems, public health and economy. To date several observational epidemiological studies consistently found that vitamin D deficiency, measured as low levels of circulating 25-hydroxyvitamin D, is associated with cardiovascular diseases, diabetes, certain cancers, autoimmune diseases and many infectious d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 160 publications
0
6
0
Order By: Relevance
“…If the criteria change using the values by the Food and Nutrition Board, children with insufficiency (level between 12 and 20 ng/ml) could participate in a new trial and only patients with vitamin D deficiency (<12 ng/ml) would be excluded. In the recent review by Briceno Noriega et al, several recommendations are made for future research ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the criteria change using the values by the Food and Nutrition Board, children with insufficiency (level between 12 and 20 ng/ml) could participate in a new trial and only patients with vitamin D deficiency (<12 ng/ml) would be excluded. In the recent review by Briceno Noriega et al, several recommendations are made for future research ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it inhibits inflammatory processes (Bikle 2022 ). Briceno Noriega and Savelkoul ( 2022 ) confirmed that VD plays an important role against the endemic phase of COVID-19 respiratory tract infection by acting as an immune modulator. It would play a protective role in the endemic phase of COVID-19 by stimulating the cellular receptor angiotensin converting enzyme 2 (ACE2)/Ang (1–7)/Mas G and inhibiting the expression of renin and the angiotensin II receptor type I (AT1R) axis.…”
Section: Resultsmentioning
confidence: 91%
“…Multiple articles report that a high rate of vitamin D deficits exists among various cases deemed COVID-19 positive. In addition, many report a probable vitamin D deficit that raises the risk of more severe infection responses than not, 25,26 although this is not an accepted fact to any degree. However, other data are supportive of this aforementioned view because they show that there does appear to be a high rate of deficient vitamin D levels in the acute or post-COVID-19 studied groups although this is not well correlated or consistent.…”
Section: Key Findingsmentioning
confidence: 99%